Determinan Profitabilitas Perusahaan Makanan dan Minuman Tahun 2019-2023 - Selvia Febrianti; Siti Sundari (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2025)
This research investigates the effect of receivables turnover, inventory turnover, and working capital turnover on the profitability of companies operating in the food and beverage sub-sector listed on the Indonesia Stock Exchange between 2019 and 2023. A total of 16 companies were chosen as the sample using purposive sampling based on predetermined criteria. Utilizing a quantitative method with panel data, the analysis was carried out through a fixed effect panel regression model using EViews software. The findings reveal that receivables turnover significantly and positively contributes to profitability, indicating that improved receivables efficiency can enhance a firm’s earnings. On the other hand, inventory turnover and working capital turnover were found to have no meaningful impact on profitability, likely due to unstable management practices and considerable fluctuations observed during the study period.